Comportamiento del consumidor digital en los residentes de las ciudadelas de la periferia de la ciudad de Babahoyo. - Carriel Maldonado, Odalys Julissa (2022)
Digital marketing has increased its influence in the purchase process, by working with completely visual tools, such as social networks. The easy dissemination of information generated by this medium is a favorable characteristic when marketing a product, due to the scope and influence that originates in the consumer by indirectly implanting the feeling of need and consequently giving thought and even leading to complete the purchase of a product. Consumer behavior has been exposed to various changes over time, being forced to adapt to strategic digital behavior, which is why marketing as an independent discipline in the field of marketing represents a circumstantial element in behavior of the consumer. The need for methods by which a consumer searches for and can acquire a product has modified the purchase process from both the seller's and the buyer's perspective in the face of the evident change from traditional marketing to digitalized marketing. The location of the residents of the citadels on the outskirts of the city of Babahoyo at the height of the Febres Cordero road, as they are in a rural area isolated from the city center and do not have commercial premises around them, generates a notorious problem in a consumer society such as this community, which has been forced to investigate alternatives to satisfy needs, in this way they have resorted to digital marketing.